2009
DOI: 10.1177/0022429408329134
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Beginning Instructional Grade on String Student Enrollment, Retention, and Music Performance

Abstract: The purpose of this study was to investigate three primary variables concerning the starting grade level of beginning string instruction in public schools: (a) initial enrollment, (b) retention data for both the end of the first year and at the seventh-grade year of instruction, and (c) music performance level in the seventh grade. Secondary variables including schedule of instruction, decision makers, grade-level organization, and private lessons also were examined. Research objectives were developed to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 11 publications
2
17
0
Order By: Relevance
“…Kansas string programs also look similar to string programs nationally. Congruent with the results reported by Doerksen and Delzell (2000), Hamann (1998), Hamann et al (2002), Hartley andPorter (2009), Horvath, (1995), and Schmidt et al, (2006), most Kansas string programs offer first-year string instruction in either fourth, fifth, or sixth grade. Hamann (1998), Hamann et al (2002), and Horvath (1995) found that more than half of string teachers reported heterogeneous class groupings for first-year strings classes.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Kansas string programs also look similar to string programs nationally. Congruent with the results reported by Doerksen and Delzell (2000), Hamann (1998), Hamann et al (2002), Hartley andPorter (2009), Horvath, (1995), and Schmidt et al, (2006), most Kansas string programs offer first-year string instruction in either fourth, fifth, or sixth grade. Hamann (1998), Hamann et al (2002), and Horvath (1995) found that more than half of string teachers reported heterogeneous class groupings for first-year strings classes.…”
Section: Discussionmentioning
confidence: 76%
“…In many cases teachers stated that the starting grade had been pushed back by at least one grade level. Hartley and Porter (2009) suggest that delaying the starting grade of first-year string students may actually increase overall retention in orchestra programs, and that depending on a number of factors such as class meetings per week and number of minutes per class meeting, delaying the starting year has little impact on overall student performance. A number of factors can contribute to school districts making changes to starting grade level for strings, however this appears to be a trend throughout Kansas.…”
Section: Discussionmentioning
confidence: 99%
“…In some schools, instrumental performance instruction (e.g., band, orchestra) may be offered during the regular school day, before or after school, or during lunch or recess. Most string instrument programmes in the USA start in the 4th grade, while most band programmes start in the 5th grade (Hartley & Porter, 2009). …”
Section: Music In Elementary Schoolmentioning
confidence: 99%
“…Thus, future research could fruitfully focus on more elaborate analyses of individual differences in responses to technology such as NETEM, covering not only enjoyment of and persistence with ensemble music making, but also individual musical development and practice behaviour. Moreover, all of these factors need to be considered within sociocultural context, given that, as well as school instructional approaches, family characteristics, socioeconomic status, gender, and culture are all likely to relate to children’s expectations, beliefs, goals, values, and behaviours in the musical domain (see Hartley & Porter, 2009; Hawkinson, 2015; Kinney, 2010; McPherson & O’Neill, 2010).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Research shows that a wide range of factors play a role in children’s persistence with playing a musical instrument (e.g., Hartley & Porter, 2009; Hawkinson, 2015; Kinney, 2010), and perceptions of musical ability appear to play a role in orchestral dropout for at least some students (Cook, 2013). Given the high rates of dropout from musical instrument learning, it is not surprising that researchers have called for supportive and flexible teaching environments which facilitate the development of creativity (Hallam, 2010).…”
mentioning
confidence: 99%